Сравнительный анализ стратегий Германии в ответ на военно-политические кризисы 2008 г. и 2014 г. (2008 թ. և 2014 թ. ռազմաքաղաքական ճգնաժամերի ընթացքում Գերմանիայի ռազմավարությունների համեմատական վերլուծություն) - Սարկիսյան Դավիդ (YSU Journal of International Affairs, 2016)
This papers deals with the comparative analysis of German political reactions to the military-political crises involving Russia that occurred in Georgia (2008) and Ukraine (2014). The role of mutual perceptions of foreign political goals of Germany and Russia in stipulating the strategic course towards each other has been discussed. The current stalemate phase of the Ukrainian crisis was modeled with the application of game theoretic analysis. A model-based forecast was made regarding the future trajectory of developments in Russo-German relationship in the context of the Ukrainian conflict.